2020
DOI: 10.1001/jamanetworkopen.2020.6368
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and Treatment of Non–Small Cell Lung Cancer in the Age of Deep Learning

Abstract: Lung cancer is both the most common and the most deadly cancer, with more than 2 million cases diagnosed worldwide in 2018 per Global Cancer Observatory estimates and with non-small cell lung cancer (NSCLC) accounting for the great majority of cases. The 8th edition of the American Joint Committee on Cancer TNM stage groupings represents the most well-validated prognostic metric for NSCLC. However, a variety factors unaccounted for by these TNM stage groupings affect outcome, from patient-specific factors such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Age is associated with the incidence and prognosis of many cancers, and studies have shown that age is an independent risk factor for cancers such as non-small cell lung cancer and breast cancer 11 , 12 . Previous studies showed that about 90% of bladder cancer patients are over 55 years old, and the average age at diagnosis is 73 years old 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Age is associated with the incidence and prognosis of many cancers, and studies have shown that age is an independent risk factor for cancers such as non-small cell lung cancer and breast cancer 11 , 12 . Previous studies showed that about 90% of bladder cancer patients are over 55 years old, and the average age at diagnosis is 73 years old 13 .…”
Section: Discussionmentioning
confidence: 99%
“…These models can capture non-linear relationships that traditional statistical methods may miss. At present, particular attention is paid to deep learning and its contribution to cancer research; see, for instance [24]. Here, however, we would like to briefly cite some research sectors in which our neural approach to small datasets can benefit cancer studies.…”
Section: Possible Applications In the Medical Fieldmentioning
confidence: 99%
“…Age plays a major role in the onset, progression and prognosis of disease [9] . The immune system of older people undergoes a remodeling process during ageing compared to younger people, which reduces the function and anti-tumor capacity of various immune cells, thereby reducing the e cacy of immune checkpoint inhibitors [10][11] . Therefore, a systematic evaluation and Meta-analysis on the therapeutic effects of immune checkpoint inhibitors on non-small cell lung cancer patients with different ages was conducted in this study, with a view to providing a reference for clinical treatment.…”
Section: Introductionmentioning
confidence: 99%